Rice Husk Ash Modified with Vanadium Pentoxide - Rodrigues, Isaias Alves; de Lira, Stéfane Oliveira; Estrela, Tiago dos Santos; de Castro, Cailon França; Braga, Valdeilson Souza (Orbital: The Electronic Journal of Chemistry, 2017)
Rice husk collected in Barreiras City, Bahia, Brazil was converted to rice husk ash (RHA) by acidic or basic leaching, followed by calcination. The resulting RHA was modified with vanadium pentoxide (2, 5, or 10 mass% of V2O5). The modified RHA samples were characterized by X-ray diffraction (XRD) and Fourier transform infrared spectroscopy (FTIR). RHA exhibited FTIR bands associated with silica. After modification of acid-leached RHA with vanadium, the XRD data indicated the formation of V2O5 phases. Base-leached RHA modified with vanadium pentoxide showed the presence of the V2O5 phase only in the sample containing 10 mass% V2O5. The FTIR data indicated the formation of cristobalite, where bands associated with Si-O-V interactions were observed only for the sample with 10 mass% V2O5 prepared with acid-leached RHA. DOI: http://dx.doi.org/10.17807/orbital.v9i2.916